2018
DOI: 10.6061/clinics/2018/e412s
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and blood cancers

Abstract: Type 2 diabetes mellitus and cancer are correlated with changes in insulin signaling, a pathway that is frequently upregulated in neoplastic tissue but impaired in tissues that are classically targeted by insulin in type 2 diabetes mellitus. Many antidiabetes treatments, particularly metformin, enhance insulin signaling, but this pathway can be inhibited by specific cancer treatments. The modulation of cancer growth by metformin and of insulin sensitivity by anticancer drugs is so common that this phenomenon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 165 publications
0
24
1
Order By: Relevance
“…This is the first human study investigating the risk of leukemia after metformin use in T2DM patients. Unlike many previous studies that showed beneficial effects of metformin on the prevention of solid cancers (14) and some recent in vitro studies suggesting an inhibitory effect of metformin on the growth of leukemic cells (11,12), the findings of the present study did not support a beneficial effect of metformin on leukemia in human beings (Tables 2 and 3). In the main analyses, the risk of leukemia was neutral while comparing metformin (+) versus metformin (-) in either the intention-totreat or the per-protocol analysis ( Table 2).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is the first human study investigating the risk of leukemia after metformin use in T2DM patients. Unlike many previous studies that showed beneficial effects of metformin on the prevention of solid cancers (14) and some recent in vitro studies suggesting an inhibitory effect of metformin on the growth of leukemic cells (11,12), the findings of the present study did not support a beneficial effect of metformin on leukemia in human beings (Tables 2 and 3). In the main analyses, the risk of leukemia was neutral while comparing metformin (+) versus metformin (-) in either the intention-totreat or the per-protocol analysis ( Table 2).…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, we cannot readily interpret the findings of metformin benefits on leukemic cells derived from in vitro studies (6,7,11,12). Secondly, an overall neutral effect of metformin on leukemia risk ( Table 2) and the potentially higher risk observed in patients in persistent use (per-protocol analyses, Models VI and VII, Table 3), calls for a cautious attention to the ongoing preclinical trials investigating the use of metformin as a therapeutic agent for leukemia (14). Thirdly, the possibility of differential responses to AMPK activators (such as metformin) between solid tumors and leukemia opens a new interesting venue for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together these data reflect the high involvement of mitochondria in the resistance to the drugs commonly used for the treatment of cHL, making them a highly favorable target for therapeutic manipulation via biguanides and metformin ( 99 ).…”
Section: Increased Ox-phos In Hodgkin Lymphoma Is Associated To Revermentioning
confidence: 83%
“…Therefore, the role of these confounders in the association between T2DM and leukemia risk remains imprecise. Second, recent research has highlighted the inverse association of some antidiabetic drugs, such as metformin, with the risk of certain cancers [46][47][48][49]. Unfortunately, the role of these drugs in the relationship between DM and leukemia risk has rarely been elucidated in the included studies.…”
Section: Discussionmentioning
confidence: 99%